Dampak Remaja Putus Sekolah terhadap Masyarakat di Desa Tunbes Nusa Tenggara Timur - Priskila Anin (PENSOS : Jurnal Penelitian dan Pengabdian Pendidikan Sosiologi, 2023)
The purpose of this study was to determine the social impact of teenagers dropping out of school, and (b) the factors that caused teenagers to drop out of school in Tunbes village, East Nusa Tenggara. This Research was the qualitative method. The subjects consisted of dropouts of teenagers, parents, and traditional leaders. Data collection techniques used in this study were observation, interviews, and documentation. Data analysis techniques used data reduction, data presentation, conclusion drawing, and verification. The results of this study indicate that the negative impact of dropping out of school is the loss of a future or ideals. It is difficult to find a job because it does not have a diploma certificate and lacks knowledge. They become a burden on the government in developing countries, and the positive impact is helping parents at home to fulfil financially. Meanwhile, the factors that cause teenagers to drop out of school are families with low economic income, children hanging out with peers who are no longer in school and a lack of interest in learning due to the long distance from home to school.